2022
DOI: 10.1186/s12889-022-12713-z
|View full text |Cite
|
Sign up to set email alerts
|

Mental health problems and their related factors among seafarers: a scoping review

Abstract: Background Seafarers are often reported to be engaged in a dangerous physical and psychosocial work environment. However, mental health status among seafarers has not been focused on compared with physical health issues. Systematic, comprehensive reviews of mental health problems and their relevant factors are lacking. This review aimed to clarify beneficial approaches to the mental health problems faced among seafarers using a scoping review to systematically map the evidence regarding mental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 62 publications
0
21
0
1
Order By: Relevance
“…H 6 : To explore the association between burnout and job satisfaction. The hypothesis suggests that higher levels of burnout may be associated with lower levels of job satisfaction among yacht crew members (62). H 7 : To investigate the potential relationship between burnout and fatigue.…”
Section: Methodsmentioning
confidence: 99%
“…H 6 : To explore the association between burnout and job satisfaction. The hypothesis suggests that higher levels of burnout may be associated with lower levels of job satisfaction among yacht crew members (62). H 7 : To investigate the potential relationship between burnout and fatigue.…”
Section: Methodsmentioning
confidence: 99%
“…A large body of literature has explored various risk factors affecting seafarers’ mental health, demonstrating that the working environment at sea exposes seafarers to stress and psychological harm ( Abila and Acejo, 2021 , Abila and Tang, 2014 , Iversen, 2012 , Jonglertmontree et al, 2022 , Sampson and Ellis, 2021 ). Nevertheless, due to the stigma associated with mental health problems, it is suggested that seafarers are reluctant to acknowledge them and seek support.…”
Section: Literature Reviewmentioning
confidence: 99%
“…36 Seafarers' mental health and well-being gained special attention with the COVID-19 pandemic, and 5 literature reviews have been published since March 2019. [37][38][39][40][41] These reviews exhaustively analyzed the factors affecting seafarers' mental health and well-being during the period. The literature mainly focused on describing the factors that contribute to either improving seafarers' mental health or preventing seafarers from becoming mentally ill. 42 The study of seafarers' mental health and its screening and monitoring has been the subject of significant attention during the COVID-19 period and post-pandemic.…”
Section: Introductionmentioning
confidence: 99%